Analisis Kegagalan Sistem Pelumasan Piston pada Diesel Generator Nomor 1 di Kapal MV. Hanglima - Moh. Rifqi Bagus Wahyudi; Sugeng Marsudi; Rodlitul Awwalin (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
This study analyzes the causes of piston lubrication system failure and its impact on the performance of Diesel Generator No. 1 aboard MV. Hanglima. The lubrication system is essential for reducing friction, cooling engine components, and preventing wear to ensure reliable diesel engine operation. This research employed a qualitative descriptive approach using direct observation in the engine room, interviews with engine crew members, and documentation from engine logbooks and engine disassembly results. The findings show that the engine initially operated normally, but a significant increase in fresh water and lubricating oil temperatures, followed by a drop in lubricating oil pressure below the minimum operating limit of 2.5 bar, activated the Low Lubricating Oil Pressure alarm. This condition caused the engine speed to decrease from 1200 RPM to approximately 700 RPM, reducing both frequency and electrical power output. Engine disassembly revealed that the failure was primarily caused by a blocked piston cooling jet in Cylinder No. 3, contaminated oil filters, sludge accumulation in the oil sump, and wear on the piston and cylinder liner. Regular preventive maintenance is therefore essential to ensure stable and reliable diesel generator performance.